Dacsee Company: Expanding into Carpooling in Malaysia - Jarkko Ylitalo; Daisy Mui Hung Kee; Olli Juvonen; Saana Kaario; Iiro Järveläinen; Nikita Mukul Nijasure (Journal of the Community Development in Asia (JCDA), 2019)
For our research topic of Nusantara project, we chose Malaysian based e-hailing application Dacsee. Currently Dacsee company’s most important revenue source is the taxi service through their mobile application. In this paper, we are suggesting that Dacsee should de-risk their business and expand their business model to ride sharing (ie. carpooling). Furthermore, by expanding their business, Dacsee will get access to different revenue sources, gain economies of scale benefits and leverage first-mover advantage. First, the Dacsee Company is introduced. After that, a critical analysis of the economic feasibility of our idea is analyzed from multiple perspectives. Some of the analysis done are for example Porter Five Forces analysis and VRIO analysis. As a result of our analyses we’ll suggest Dacsee Company to include carpooling to their product catalogue. By aggressive marketing and expanding their services quickly nationwide, they will gain temporary competitive advantage over rival companies. If Dacsee simultaneously utilizes their own cryptocurrency and promotes customer revenue they will be able to create customer lock-in in the market renowned by fierce competition. The purpose of this study was to figure out improved ways for Dacsee to conduct their business in Malaysia.